Analysis of Communication, Knowledge Management, Teamwork, Ability, and Performance of Private Sector Employees in the City of Semarang - Tyoso, Jaluanto Sunu Punjul; Sukardi, Sukardi; Mahesa, Deewar (PT. Riset Press International, 2024)
The objective of this study is to scrutinize the impact of communication, knowledge management, teamwork, and capability on the performance of employees. The research utilized a quota sampling technique, involving a total of 344 employees. The factors under investigation were communication, knowledge management, teamwork, capability, and employee performance. The results from the hypothesis testing indicated that communication significantly improves employee performance. Moreover, it was discovered that capability considerably augments employee performance via knowledge management and teamwork. The research emphasizes the crucial contribution of capability in enhancing employee performance. It was also verified that knowledge management and teamwork significantly contribute to employee performance. To sum up, this study offers important perspectives on the elements affecting employee performance, underlining the significance of communication, knowledge management, teamwork, and capability.